2005
DOI: 10.1021/jp051383w
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interfacial Organization in Surface Monolayers Using Tethered Pyrene. 2. Spectroscopy and Motional Freedom of the Adsorbates

Abstract: We have studied the steady-state and time-resolved emission spectroscopy of the pyrene-containing monolayers reported in the previous article, where in this work we have bound the monolayers to SiO(x). We find that these monolayer structures are sensitive to the identity of the solvent overlayer, with the solvent playing a significant role in the organization of the surface-bound monolayers. We discuss our findings in the context of the known polarity dependence of the pyrene emission spectrum and find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Figure 6 presents the resulting steady-state fluorescence spectra both of a suspension of nanoparticles in water (Figure 6 a) and of dry nanoparticles deposited on quartz (Figure 6 b). The emission spectra of modified nanoparticles are qualitatively similar to those reported for 1-amidopyrene hexanoate bound to ITO and silica www.chemeurj.org surfaces, [11,21] indicating that the nanoferrites are now decorated with this fluorophore. Steady-state spectroscopy on this system reveals the presence of excimers in the adlayer bound to the nanoferrite surface.…”
supporting
confidence: 72%
“…Figure 6 presents the resulting steady-state fluorescence spectra both of a suspension of nanoparticles in water (Figure 6 a) and of dry nanoparticles deposited on quartz (Figure 6 b). The emission spectra of modified nanoparticles are qualitatively similar to those reported for 1-amidopyrene hexanoate bound to ITO and silica www.chemeurj.org surfaces, [11,21] indicating that the nanoferrites are now decorated with this fluorophore. Steady-state spectroscopy on this system reveals the presence of excimers in the adlayer bound to the nanoferrite surface.…”
supporting
confidence: 72%
“…There are two striking features about this figure that should be noticed. First, the well-known pyrene scale based on the intensity ratio of the pyrene emission band 1 (at 373 nm) to the emission band 3 (at 383 nm) for sensing polarity 36 that has been observed for some pyrene-modified adlayers 35,37,38 is not shown in the present case. As to the two monomer emission bands at 382 and 402 nm observed for the present film, there is no regular correlation of the intensity ratio (I 382 /I 402 ) with the polarity of the tested solvents.…”
Section: Surface Characterization Of Film Py-eoamentioning
confidence: 65%
“…The covalent attachment of polycyclic aromatic hydrocarbons (PAHs) to selected substrates has attracted significant research interest [1][2][3][4] because the spectroscopic and electrochemical properties of PAHs are sensitive to their immediate environment, providing a useful chemical transducer for sensors [1,5,6]. Reinhoudt and coworkers have designed several thin film materials containing bound chromophores that are useful because of their fluorescence response to cationic [7][8][9], anionic [9], and neutral species [10].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the difference in these microenvironments, the selectivity and sensitivity of the modified surfaces for specific analytes can, in principle, be controlled in this manner. The Blanchard group has constructed several molecular assemblies where pyrene molecules were co-immobilized with other functionalities [2,25]. These results showed that the co-immobilization of stearic acid with pyrene provided a non-polar environment for the pyrene moieties, and that the addition of optical donor/acceptor couples (pyrene/perylene) and redox couples (pyrene/ferrocene) modulated energy transfer.…”
Section: Introductionmentioning
confidence: 99%